HUBUNGAN PAJANAN PESTISIDA DENGAN KEJADIAN HIPERTENSI PADA PETANI HORTIKULTURA DI DESA GERLANG KECAMATAN BLADO KABUPATEN BATANG - Fitria Agustina; Suhartono Suhartono; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The use of pesticide on agricultural land is common for eradicate plant-disturbing organisms to increase agricultural productivity. High use of pesticide can have adverse health effects. Active ingredients contained in the pesticides causing impaired of cholinesterase enzymes which can cause hypertension. Gerlang village is on of the most frequently village used of pesticides. This research have purpose to analyze the relationship beetwen of pesticide exposure with hypertension in horticultural farmers in Gerlang village. This research uses observational method with cross-sectional approach. Population of this research is all farmers in Gerlang village and take 70 respondents as a sample. Data were analyzed using chi-square test. The result of statistical test shows that there is a correlation beetwen level of using pesticide (p=0,032) and pesticide type (p=0,021) with hypertension. There is no correlation between length od using pesticide (p value is cannot be shows because of constant answer) and management of pesticide use (p=0,018) with hypertension. From this research to anticipated the impact of using pesticide that require routinely spraying through the use of personal protective equipment during work.